“Quem fala que não leva o trabalho pra casa ‘tá’ mentindo”: o processo de subjetivação das/os policiais penais - Araújo, Isabela Cristina Alves de (Universidade Federal de São Carlos, 2024)
This thesis seeks to understand how the process of subjectivation of male and female prison officers occurs based on their work in correctional institutions, using the concept of “prisonization” developed by Clemmer as a theoretical basis. In addition, the work seeks to uncover whether there are differences in the perceptions of women and men. In other words, the aim is to articulate gender and the construction of a prisonized subjectivity. For that purpose, a mixed-methods methodology was employed. From a qualitative perspective, 57 interviews were conducted with prison officers based in the Metropolitan Region of Belo Horizonte, where 22 were women and 35 were men. From a quantitative perspective, 91 structured questionnaires were answered, 53 by male prison officer and 38 by female prison officer. The analyses indicated that custodial techniques are transformed into a self-techniques, in which the officers guide their conduct both inside and outside the prison. A prisonized subjectivity is the construction and adoption of the prison culture that is supported by distrust, fear, violence, hostility, hyper-vigilance, valorization of the performances of masculinity.
“Anyone who says they don’t bring work home is not telling the truth”: the subjectivation of penal officers
Keywords: Prisionização; Polícia penal; Sistema prisional; Militarização; Gênero; Prisonization; Prison officer; Penitentiary system; Militarization; Gender; CIENCIAS HUMANAS::SOCIOLOGIA